Fatores críticos de sucesso que afetam a permanência estudantil na universidade: um estudo de caso dos estudantes ingressantes nos cursos de engenharia da Universidade Federal de São Carlos UFSCAR - Biscegli, Murillo (Universidade Federal de São Carlos, 2026)
The work entitled “Critical Success Factors Affecting Student Retention at the University: A Case Study of Students Entering Engineering Courses at the Federal University of São Carlos (UFSCAR)” aimed to analyze the factors impacting dropout rates in undergraduate engineering courses at UFSCAR. To this end, a model focused on identifying Critical Success Factors (CSFs) from the students' own perspective was developed and validated. The goal is to provide institutional managers with tools to identify key areas for improvement, contributing to more effective strategic, operational, and institutional management, as well as providing students with a guide to the actions taken by the institution. The proposal also aims to reduce inequalities and foster the production of scientific and technological knowledge capable of improving students' quality of life. In this context, this master's dissertation sought to answer the following question: “What are the Critical Success Factors for undergraduate engineering courses at UFSCAR?” The main objective was to identify and group the relevant CSFs for these courses. Specifically, through a literature review, the study sought to identify the common Critical Success Factors (CSFs) for these courses, with the aim of analyzing, grouping, and discussing them in light of data collected through questionnaires administered to incoming Engineering students at the Federal University of São Carlos (UFSCAR), located in the city of São Carlos, SP. Based on the data analysis, it was possible to propose a set of specific CSFs for undergraduate Engineering courses, with the potential to support the management of these programs and offer support to students. Finally, a Technological Product proposal for a retention support system to monitor student dropout rates at the University is presented. Keywords: Critical
Critical success factors affecting student retention at university: A case study of students entering engineering courses at the Federal University of São Carlos (UFSCAR)
Keywords: Fatores críticos de sucesso; Educação; Evasão; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade